A C21-Steroidal Glycoside Isolated from the Roots of Cynanchum auriculatum Induces Cell Cycle Arrest and Apoptosis in Human Gastric Cancer SGC-7901 Cells. (19th December 2013) - Wang, Yi-Qi; Zhang, Shui-Juan; Lu, Hong; Yang, Bo; Ye, Liang-Fei; Zhang, Ru-Song
Abstract : Caudatin 3-O-β -D-cymaropyranosyl-(1 → 4 )-β -D-oleandropyranosyl-(1 → 4 )-β -D-cymaropyranosyl-(1 → 4 )-β -D-cymaropyranoside (CGII) is one of the C21 -steroidal glycosides isolated from the roots of Cynanchum auriculatum ROYLE ex WIGHT. This study aimed to determine the cell growth, cell proliferation, and apoptotic cell death of human gastric cancer cells after CGII treatment. MTT assay was used to determine cell growth; fluorescence-activated cell sorting analysis was used to evaluate cell cycle distribution and apoptotic cell death. Immunoblotting was applied for measuring the expression of proteins involved in the cell cycle progression. The activities of caspase-3, -8, and -9 were detected by colorimetric caspase activity assays. CGII inhibited cell growth of human gastric cancer SGC-7901 cells in a concentration- and time-dependent manner. Treatment of SGC-7901 cells with CGII resulted in G1 phase cell cycle arrest, accompanied with decreased expression of cyclin D1 and cyclin-dependent kinases 4 and 6. CGII induced cell apoptosis and activated caspase-3, caspase-8, and caspase-9. In contrast, pan-caspase inhibitor z-VAD-fmk partially abolished the CGII-induced growth inhibition of SGC-7901 cells. In conclusion, CGII inhibits cell growth of human gastric cancer cells by inducing G1 phase cell cycle arrest and caspase-dependent apoptosis cascades.